Dakwah Kolaboratif: Model Alternatif Komunikasi Islam Kontemporer - Anis Bachtiar, M. (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2013)
Proselytizing activities in Indonesia have been predominantly based on two approaches, structural and cultural. This article discusses the synergy of the two main–stream approaches, which can be called a collaborative method in proselytizing. It argues that this collaborative approach is able to cover up the weaknesses of the dicho–tomy in structural and cultural propagation. In addition, this collaborative approach can be made use of to deal with different kinds of society; all the more so as lately fundamentalists conduct aggressive movements, challe–nging moderate Islam in this country. The collaborative approach is expected to be an alternative option for optimizing the out-put of proselytizing.Keywords: collaborative proselytizing, structural and cultural approaches, synergy.————————————————————————–Aktivitas dakwah di Indonesia saat ini didominasi oleh dua pendekatan, yakni struktural dan kultural. Artikel ini membahas sinergi dua mainstream pendekatan ter–sebut, yang disebut dakwah kolaboratif. Tulisan ini ber–pendapat bahwa pendekatan dakwah kolaboratif mampu menutupi kelemahan pendekatan struktural dan kultural yang dilakukan secara dikotomis. Selain itu, dakwah kolaboratif dianggap lebih mampu masuk ke seluruh ranah masyarakat. Apalagi belakangan ini kelompok fundamen–talis melakukan gerakan-gerakan agresif yang mengkha–watirkan keberlangsungan penyebaran paham Islam moderat di negeri ini. Pendekatan dakwah kolaboratif ini diharapkan mampu menjadi pilihan alternatif untuk optimalisasi out-put dakwah.Kata Kunci: dakwah kolaboratif, pendekatan structural dan kultural, sinergi.